Respuestas

2014-03-05T02:34:34+01:00
1) 13+14+15=42
Ahora mira la expresamos
x primer numero
x+1 segundo numero
x+2 tercer numero

x+(x+1)+(x+2)=42
3x+3=42
3x=42-3
3x=39
x=39/3
x=13
Reemplazamos
x primer numero =13
x+1 segundo numero=13+1=14
x+2 tercer numero = 13+2=15

2)13+15+17=45
Ahora mira la expresamos
x primer numero
x+2 segundo numero
x+4 tercer numero

x+(x+2)+(x+4)=45
3x+6=42
3x=45-6
3x=39
x=39/3
x=13
Reemplazamos
x primer numero =13
x+1 segundo numero=13+2=15
x+2 tercer numero = 13+4=17